GE_GERICHTE P/19602/2020 vom 28. September 2023 - GE Cour de justice (2023)
DISPOSITIONS PÉNALES DE LA LCR;ERREUR DE DROIT(DROIT PÉNAL) | CP.177; CP.286; LCR.97.al1.lete; LCR.97.al1.letf; LCR.90; LCR.91a.al1; CPP.389.al1; CPP.389.al3; CP.21; CP.54